Rethinking the Disability Digital Divide in Relations to Visual Disability in Sri Lanka - Wedasinghe, N.; Wicramarachchi, R. (Faculty of Social Sciences, University of Kelaniya, Sri Lanka, 2015)
People who are blind or visually impaired do not have equal opportunities to access information technology and internet access compared to the non disabled population in Sri Lanka. The level of usage of ICT by the disabled and non disabled are different in developed and developing countries. The purpose of this study is to find the reasons behind the digital divide among the people with visual disabilities in Sri Lanka and proposed solutions to eliminate digital divide among the Sri Lankan visually impaired differently able community. This study was conducted based on the literature behind the Digital divide, social construction of disability, The digital age, the development of information technology and Internet related technology and Other countries and Sri Lankan corporate policies related to information technology and main problems and issues faced by the visually impaired people when accessing ICT and Internet. In order to collect information on the Sri Lankan disability digital divide, interviews were conducted with a range of government representatives and more than 75 visually impaired civil and military computer users in Sri Lanka. As a result of this study it has been indicated that compared to other developed nations, Sri Lanka has also addressed the issue by implementing Nanasala project through ICTA and improving the telecommunication infrastructure with in the country and many other projects via private and public institutions with in the country. Survey results indicated that many Sri Lankans with disabilities are reluctant to use Information technology due to poverty, lack of awareness, lack of interest and their social and cultural backgrounds and also as their first language is not very well supported by the computer system. These factors are highly co-related with digital disability in Sri Lanka. Conclusions and recommendations are made by proposing implementation of several projects under the supervision of the central government. They are to introduce a web portal for visually disabled people with language support, more training and awareness of the ICT among this community, encourage and develop screen reader software which can support first languages such as Tamil and Sinhala.
Keywords: Digital age; Digital divide; Disability; Digital accessibility